2012
DOI: 10.3382/ps.2010-01293
|View full text |Cite
|
Sign up to set email alerts
|

The probiotic Bacillus licheniformis ameliorates heat stress-induced impairment of egg production, gut morphology, and intestinal mucosal immunity in laying hens

Abstract: We investigated the effect of a 12-d exposure to 34°C plus dietary inclusion of the probiotic Bacillus licheniformis on the egg production, gut morphology, and intestinal mucosal immunity of laying hens. Ninety-six commercial hens (Hy-Line Brown) at the age of 60 wk were randomly allocated to 4 groups. After a period of laying rate adjustment (14 d), all the hens were subjected to 2 temperature treatments (12 d). Birds in 1 group were raised at 21°C and fed a basal diet, and birds in the other 3 groups were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
145
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(189 citation statements)
references
References 42 publications
18
145
2
3
Order By: Relevance
“…Exposure to heat stress resulted in a decline in the IEL count in all segments of the small intestine. Similar observations were made in broilers by Deng et al, (2012). However, these results are in contrast with those reported by Ashraf et al (2013) and QuinteiroFilho et al (2010).…”
Section: Discussioncontrasting
confidence: 57%
“…Exposure to heat stress resulted in a decline in the IEL count in all segments of the small intestine. Similar observations were made in broilers by Deng et al, (2012). However, these results are in contrast with those reported by Ashraf et al (2013) and QuinteiroFilho et al (2010).…”
Section: Discussioncontrasting
confidence: 57%
“…The addition of beneficial bacteria to a diet can recover the intestinal integrity, thereby increasing nutrient bioavailability and absorption (Burel & Valat, 2009;Deng et al, 2012). Probiotics also improved gut health, which directly improved the birds' health and performance (Burel & Valat, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 99%
“…It was revealed that chickens exposed to acute heat stress (30 °C/24 h) presented a reduction of the ileum's crypt depths but no significant differences in the villus height and villus: crypt ratio (Burkholder et al), this showed that heat stress via changing the intestinal morphology and structure increased the organism risk of illness. Compared with birds kept at 21 °C, birds kept at 34°C had decreased villus height, ratio of villus height to crypt depth and fewer intraepithelial lymphocytes (Deng et al, 2012), suggested that thermal stress damaged the normal intestinal health. In our study, at day 35, ducks in HS group had deeper crypt depth than those in CrPic group in ileum.…”
Section: Discussionmentioning
confidence: 99%